Structural and morphological characterization of chemical bath deposition of FeS thin films in the presence of sodium tartrate as a complexing agent. - Kassim, Anuar; Ho, Soon Min; Loh, Yean Yee; Nagalingam, Saravanan (2010)
In this paper, we presented the results of X-ray diffraction and scanning electron microscopy of the ironsulphide thin films prepared using a simple and cost effective chemical bath deposition method. The effectsof solution concentration and pH on the structural and morphological properties of thin films were studiedin the presence of sodium tartrate as a complexing agent. The thin films deposited using higher solutionconcentration showed higher number of FeS peaks and larger grain size according to X-ray diffraction andscanning electron microscopy results, respectively as compared with other solution concentrations. On theother hand, when the thin films were deposited at higher pH, the number of FeS peaks reduced to two peaksand the films showed incomplete coverage of material over the surface of the substrate with the smaller grainsize.